2013
DOI: 10.3928/23258160-20130909-06
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Systemic Anticoagulation and Rate of Intraocular Hemorrhage Following Intravitreal Anti-VEGF Therapy for Age-Related Macular Degeneration

Abstract: The rate of intraocular hemorrhage after intravitreal injection of anti-VEGF therapy among patients with AMD is low, and there is no significant difference between patients taking systemic anticoagulant medications at the time of injection and patients not on anticoagulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
5
1
1
Order By: Relevance
“…However, the incidence of VH in AF patients with antithrombotic medications has not been well identified. While some studies have reported that antiplatelet or anticoagulation medication increases the possibility of intraocular hemorrhage,678 others had contrary findings 910111227. In this study, while the incidence of VH was 1.45 cases per 1000 person-years in warfarin monotherapy, it increased to 8.91 cases per 1000 person-years by triple therapy.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…However, the incidence of VH in AF patients with antithrombotic medications has not been well identified. While some studies have reported that antiplatelet or anticoagulation medication increases the possibility of intraocular hemorrhage,678 others had contrary findings 910111227. In this study, while the incidence of VH was 1.45 cases per 1000 person-years in warfarin monotherapy, it increased to 8.91 cases per 1000 person-years by triple therapy.…”
Section: Discussioncontrasting
confidence: 60%
“…Vitreous hemorrhage (VH) is a potential intraocular hemorrhagic complication associated with oral antiplatelet or anticoagulant medication, such as aspirin, clopidogrel bisulfate, and warfarin sodium 6789101112. Although VH can be absorbed spontaneously, it can also result in more serious complications threatening vision, such as intraocular pressure increase and proliferative vitreoretinopathy, leading to invasive surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that anticoagulation was not associated with an increased risk of hemorrhagic or any other complication following IVI [50-52]. …”
Section: Considerations Before Injectionmentioning
confidence: 99%
“…O uso de ranibizumabe (RAZ) para tratamento de DMRI em pacientes mais idosos pode estar associado com aumento do risco de eventos hemorrágicos não oculares 31 . Não está indicada a suspensão de anti-coagulantes antes do procedimento, visto que a sua manutenção não foi associada com aumento no risco de eventos adversos hemorrágicos 32 .…”
Section: Doenças Sistêmicasunclassified